Tata Kelola dan Kepemimpinan Pendidikan dalam Meningkatkan Mutu Madrasah di Era Transformasi Digital - Meti Fatimah; Suyatman; Eko Supono (Lembaga Yasin AlSys, 2026)
Madrasah quality is an important indicator of the successful implementation of Islamic education in producing graduates who excel academically, possess strong character, and uphold Islamic values. Improving madrasah quality is determined not only by the availability of facilities and infrastructure but also by effective governance and the visionary leadership of madrasah principals. This study aims to analyze the role of educational governance and leadership in improving madrasah quality. This study employed a qualitative approach using a literature review method. Data were obtained from relevant books, scholarly articles, and regulations and were subsequently analyzed using content analysis. The findings show that madrasah governance based on the principles of transparency, accountability, participation, effectiveness, efficiency, and regulatory compliance can establish a professional educational management system. The transformational, visionary, and collaborative leadership of madrasah principals also contributes to improving teacher performance, strengthening a culture of quality, promoting learning innovation, and increasing public trust in madrasahs. This study concludes that synergy between good governance and effective educational leadership is a strategic factor in realizing excellent madrasahs that are adaptive to change and capable of competing in the era of digital transformation. These findings emphasize the importance of strengthening the principles of good governance and the leadership capacity of madrasah principals as a foundation for the sustainable improvement of Islamic education quality.